Lund in 2050 - Miskulnig, Kira (2020)
The world population increases while farmland is decreasing on a global scale. One of the core sources for the loss of agricultural land is the growth of cities. While urban sprawl is mostly associated with North America, the European Union increasingly raises awareness for the greater loss of valuable soils through development processes within its member states. The variables driving the loss of farmland differ and strongly depend on the region studied. The municipality of Lund was chosen as the case study area due to its location in an agricultural area in the south of Sweden and its strong increase in population in recent years. The main drivers identified for the area are beside the growing population, the amount of built-up area per person and governmental growth management. Possible combinations of the factors were ana-lysed and became the basis for three scenarios for the year 2050. The scenarios show possible futures depending on the focus set by the planning authorities and their ef-fects on the loss of farmland. The results show, that the municipal authorities have an important role to play in safeguarding agricultural soils. Hence taking decisions towards sustainable growth of the urban areas, can be a means to protect farmland actively. Safeguarding arable soils contributes not only to higher self-sufficiency in Swedish food production, but also to feed the growing population of the future.